An investigation of ‘powerful knowledge' in the drama curriculum: a comparative document analysis of the FET caps dramatic arts and the international baccalaureate theatre guidelines - Senekal, Nicole (School of Education, 2023)
This study sets out to investigate the notion of ‘powerful knowledge' in the Dramatic Arts curricula by comparing two curriculum documents: The Internationale Baccalaureate Theatre Guidelines and the FET CAPS Dramatic Arts Guide. Michael Young's (2010) notion of ‘powerful knowledge' has been at the heart of many research studies, curriculum theories, and educational debates in recent years, evolving into a seminal concept within the wider academic and theoretical discourse of curriculum studies. It is within this paradigm that my interest was piqued to examine the knowledge structures within the Drama curriculum and more specifically this notion of ‘powerful knowledge' within Drama as a subject. Currently there is little research to draw on from a Drama education and ‘powerful knowledge' perspective which created the gap to investigate the epistemology of the Drama curriculum and whether the notion of ‘powerful knowledge' could be connected to Drama as a subject. The study is based on a qualitative document analysis comparing two distinct Drama curricula: The National Curriculum Statement (NCS) Curriculum and assessment Policy Statement (CAPS) Dramatic Arts FET Grades 10-12, and the Internationale Baccalaureate Theatre Guidelines. The study draws on the work of Michael Young (2010, 2013) and his concepts of ‘powerful knowledge' as the key theoretical foundation along Basil Bernstein's (1975) work on ‘voice', classification and framing. The study was developed further through an additional analysis utilizing Graham McPhail's (2017) analytical dimensions. McPhail's three analytical dimensions labelled the experiential, the aesthetic and the epistemic has been developed as an analytical tool for further investigation in the Drama curricula to highlight dramatic principles that could be related to the notion of ‘powerful knowledge'.